β-Subunits Promote the Expression of Ca(V)2.2 Channels by Reducing Their Proteasomal Degradation - Waithe, Dominic (American Society for Biochemistry and Molecular Biology, 2011)
The β-subunits of voltage-gated calcium channels regulate their functional expression and properties. Two mechanisms have been proposed for this, an effect on gating and an enhancement of expression. With respect to the effect on expression, β-subunits have been suggested to enhance trafficking by masking an unidentified endoplasmic reticulum (ER) retention signal. Here we have investigated whether, and how, β-subunits affect the level of Ca(V)2.2 channels within somata and neurites of cultured sympathetic neurons. We have used YFP-Ca(V)2.2 containing a mutation (W391A), that prevents binding of β-subunits to its I-II linker and found that expression of this channel was much reduced compared with WT CFP-Ca(V)2.2 when both were expressed in the same neuron. This effect was particularly evident in neurites and growth cones. The difference between the levels of YFP-Ca(V)2.2(W391A) and CFP-Ca(V)2.2(WT) was lost in the absence of co-expressed β-subunits. Furthermore, the relative reduction of expression of Ca(V)2.2(W391A) compared with the WT channel was reversed by exposure to two proteasome inhibitors, MG132 and lactacystin, particularly in the somata. In further experiments in tsA-201 cells, we found that proteasome inhibition did not augment the cell surface Ca(V)2.2(W391A) level but resulted in the observation of increased ubiquitination, particularly of mutant channels. In contrast, we found no evidence for selective retention of Ca(V)2.2(W391A) in the ER, in either the soma or growth cones. In conclusion, there is a marked effect of β-subunits on Ca(V)2.2 expression, particularly in neurites, but our results point to protection from proteasomal degradation rather than masking of an ER retention signal.